The Study of Gastro-Oesophageal Reflux Disease (GERD) in an Urban area in Zambia - Mugala, Duncan D; Kadochi, Womba; Sikasote, Chomba; Lloyd, Godfrey (Advances in Social Sciences Research Journal, 2016)
Hiatal hernias are more common in Western countries compared to the African countries. In the Western states the frequency of hiatus hernia increases with age, from patients younger than 40 years to patients older than 70 years. This is because of muscle weakening and loss of elasticity as people age goes towards the 70s, thus this age tends to predispose to hiatus hernia. The thinking is that with decreasing tissue elasticity, the gastric cardia may not return to its normal position below the diaphragmatic hiatus following a normal swallow. Loss of muscle tone around the diaphragmatic opening also may make it more patulous. Burrkitt et al also suggest that in the Western world, fiber-depleted diet leads to a state of chronic constipation and straining during bowel movement, which could explain the higher incidence of this condition in Western countries.It is also believed that Hiatal hernias are more common in women than in men. This might relate to the intra-abdominal forces exerted in pregnancy. Para esophageal hernias generally tend to enlarge with time, and sometimes the entire stomach is found within the chest. The risk of these hernias in the West, becoming incarcerated, leading to strangulation or perforation, is approximately 5%. These tendencies are not entirely the same in Zambia . We present our findings. Key Words: Diaphragm, Epigastric, Hiatus, Hernia, Pain, Reflux.